Blood Diseases and In vitro Methods and Technologies - Nowroozi, Mahdi (Global Journal of Medical and Clinical Case Reports, 2025)
In vitro diagnostics, which appraise bodily functions or illnesses by extra-corporeal examination of materials like tissue and blood, have become increasingly important in our daily lives due to increased health consciousness and the advancement of new technology. Moreover, in addition to therapeutic applications, in-vitro diagnostics may also be used to screen for and prevent diseases. Laboratory methods and techniques have changed and have forwarded movements and developed. Laboratory hematology has a role in all aspects of patient care, from basic screening to more complex investigations in third-party care services. It also includes non-laboratory services like bone marrow transplantation and blood transfusion. Diagnosis of hematology patients correlated to the target and material that they want to find and rectify the reasons of illness, such as molecular assays that tested genetic materials and macromolecules, biochemistry assays that detected the metabolic disorders, which differentiated factors by biochemical properties and interactions, and biophysical assays that utilized the light and microscopically analyzed tools for tests. In this systematic analysis, the contemporary published articles that discuss the diagnosis of hematological diseases and demonstrate the factors of diseases that correlate with the Laboratory methods of assays. And want to indicate the correlation between the factor of illness in diagnosis analysis and laboratory methods and techniques that are utilized in diagnosis.